Microbiology of food and animal feeding stuffs. Horizontal method for the enumeration of coagulase-positive staphylococci (Staphylococcus aureus and other species). Detections and MPN technique for low numbers Part 3, (31st August 2006) - British Standards Institution,
No abstract available